Association between copayment, medication adherence and outcomes in the management of patients with diabetes and heart failure. Issue 4 (April 2017) - Gourzoulidis, George; Kourlaba, Georgia; Stafylas, Panagiotis; Giamouzis, Gregory; Parissis, John; Maniadakis, Nikolaos
Highlights: Last decade pharmaceutical spending has risen by 50% in member states of the OECD. Policy makers have taken actions in order to control pharmaceutical expenditure. Higher copayments have been adopted to curb drug spending. Lower copayments may result in higher medication adherence, which in turn may lead to better health outcomes. Chronic diseases may incur great humanistic & economic burden to health system. Abstract: Objective: To determine the association between copayment, medication adherence and outcomes in patients with Heart failure (HF) and Diabetes Mellitus (DM). Methods: PubMed, Scopus and Cochrane databases were searched using combinations of four sets of key words for: drug cost sharing; resource use, health and economic outcomes; medication adherence; and chronic disease. Results: Thirty eight studies were included in the review. Concerning the direct effect of copayment changes on outcomes, the scarcity and diversity of data, does not allow us to reach a clear conclusion, although there is some evidence indicating that higher copayments may result in poorer health and economic outcomes. Seven and one studies evaluating the relationship between copayment and medication adherence in DM and HF population, respectively, demonstrated an inverse statistically significant association. All studies (29) examining the relationship between medication adherence and outcomes, revealed that increased adherence is associated with health benefits in both DM and HF patients. Finally, the majority of studies in both populations, showed that medication adherence was related to lower resource utilization which in turn may lead to lower total healthcare cost. Conclusion: The results of our systematic review imply that lower copayments may result in higher medication adherence, which in turn may lead to better health outcomes and lower total healthcare expenses. Future studies are recommended to reinforce these findings.